The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/ijerph17031059
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Health and Well-Being in the United Nations Sustainable Development Goals: A Narrative Review of Achievements and Gaps in the Gulf States

Abstract: Background: In 2014, United Nations member states proposed a set of sustainable development goals (SDGs) to help further the millennium development goals that they had proposed in New York in 2000. Of these 13 SDGs, Goal 3 (i.e., SDG 3) was titled “Good Health and Well-Being.” This goal highlighted women’s health and well-being via two key objectives. The first, SDG 3.1, aimed to reduce maternal mortality rates (MMR) and the second, SDG 3.7, aimed to ensure access to sexual and reproductive health care service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…We argue that researchers and health care workers should give these factors as much attention as they do the physical symptoms. We assume that the absence of studies on sexual functioning indicates that the sexuality, sexual health, and sexual functioning of women and their ability to express their attitudes and feelings toward it are still considered inappropriate or taboo [ 88 ]. Similarly, the social stigma surrounding mental health constitutes a barrier to seeking help for the patient, and a barrier to researchers in asking patients about the issue [ 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…We argue that researchers and health care workers should give these factors as much attention as they do the physical symptoms. We assume that the absence of studies on sexual functioning indicates that the sexuality, sexual health, and sexual functioning of women and their ability to express their attitudes and feelings toward it are still considered inappropriate or taboo [ 88 ]. Similarly, the social stigma surrounding mental health constitutes a barrier to seeking help for the patient, and a barrier to researchers in asking patients about the issue [ 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…To find appropriate influencing factors to measure SHED, studies seek approaches to measure SHED [19]. In detail, the UN proposes the following dimensions of sustainability in education: inclusiveness, gender equality, qualified education, lifelong education, and social interactions [20,21]. Berchem proposes that competitive higher education depends on scientific research, economic contributions, and social and cultural interactions [22].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Education also enhances women's autonomy (24,42) to decide to attend services (1). Achieving equity in the SDG 3 targets for maternal, newborn, and child health outcomes depends on reaching access to education, as de ned in SDG 4 (45). Hence, media and education programs should contribute to reducing gender-based and educational inequities.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review done in low-income countries showed that inequities in maternal and child health services utilization occur in the intersection between social determinants of health (42) and poorly functioning health systems (52). Thus, addressing poverty (SDG 1), coverage and quality of education (SDG 4), ensuring gender equality (SDG 5), and ensuring good health and well-being (SDG 3) will substantially reduce inequities (45). Equity-oriented policies and interventions need to be integrated with social development programs, such as targeting poverty reduction, promoting gender equality and empowerment, and mitigating inequalities (42,50).…”
Section: Discussionmentioning
confidence: 99%